Two new species and new distribution records of robber flies (Diptera: Asilidae) from the Altai Republic (Russia) - Sakhvon, Vital (Zootaxa, 2024)
The data on the robber flies of the Altai Republic (Russia) is provided based on the results of expeditions in 2016 and 2022 and the study of museum material. Two new species, Neomochtherus proshchalykini sp. nov. and Leptogaster nikiforovi sp. nov. are described and illustrated. Currently the fauna of robber flies of the Altai Republic includes 35 species and four subspecies, with Antiphrisson mongolicus Lehr, Antiphrisson niger Lehr, Ktyr callarus callarus Lehr, Ktyr protensis Lehr and Leptogaster bivittata Lehr recorded from Russia for the first time. A key to males of Leptogaster Meigen, 1803 species from Siberia is provided.